Responsible supply chain operations : analytical modeling of emerging issues - Raychaudhuri, Avijit (2017)
Supply chain responsibility is a growing area in the operations management (OM) literature. This dissertation contributes to this literature by analyzing and explaining practical issues which are not well understood but are crucial for comprehending the implications of responsibility in supply chain operations. In this dissertation, a firm's perspective of profit maximization is taken in order to address two corporate decisions which are intrinsic to supply chain responsibility: contracting with suppliers, and investments in improving supply chain responsibility. Throughout the dissertation, non-governmental organizations (NGOs), governments, shareholders, and consumers are collectively referred to as “external entities”.